Take control of iOS 13 and iPadOS 13 - Centers, Josh (Take control., 2019)
Learn how to make the most of Apple's mobile operating systems! Version 1.2, updated 6/25/2020 Whether you use an iPad, iPhone, or iPod touch, you'll find lots to explore in Take Control of iOS 13 and iPadOS 13 by TidBITS Managing Editor Josh Centers. Learn about what's new in iOS 13 and iPadOS 13-and how to customize them to fit your needs. The latest annual update to iOS features the usual selection of new features, improved user interface, and security enhancements. It also marks the split of Apple's mobile operating system into iOS (for iPhone and iPod touch) and iPadOS (for iPad only). This is more than just a name change; with iPadOS 13, the iPad gets huge improvements that bring it much closer to the computing power and flexibility we expect from conventional computers. TidBITS Managing Editor Josh Centers is back to guide you through all the major capabilities of both operating systems in this new book. Take Control of iOS 13 and iPadOS 13 goes far beyond the new features, providing an extensive guide to getting the most out of iOS 13 and iPadOS 13. Among other things, you'll learn how to: New! Discover all the major changes in iOS and iPadOS New! Use activity views (which replace Share sheets and are for more than just sharing) New! Enable Dark Mode on your mobile device Updated! Use the new Find My app New! Make the most of improved text editing tools Updated! Use Siri and Shortcuts to do even more than before, thanks to significantly expanded capabilities New! Use accessibility improvements, including voice control and mouse support Updated! Discover the new (and existing) capabilities of Apple's upgraded apps-including Files, Mail, Maps, Messages, Notes, and Reminders Updated! Use Screen Time to make better choices about when and how you use your device New! Work with the updated iPad Home screen, Dock, and onscreen keyboard New! Learn about the new iPad multitasking capabilities, including more ways to split the screen, use multiple windows, and drag & drop between apps New! Browse the web with ease using the desktop-class Safari for iPadOS New! Use the significantly updated Camera and Photos apps to take photos and videos, apply camera effects, and organize your media Make sense of the Lock screen, Home screen, and Control Center-and customize them to meet your needs Search with Spotlight Switch between apps and use Handoff to transfer your work Navigate the App Store Understand the ins and outs of Family Sharing Manage your data ...